Análise do binômio saúde: adoecimento de professores e alunos - Soares, Valéria Antônia Benevides Solano [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work has as object the role of education in promoting health, and for that we can not dispense the analysis of health / illness of teachers and students ratio. Breaks the assumption that the creation of conditions for the formation and self-control of higher psychological functional processes within the school education imposes itself as one of the conditions that support health promotion. It is pointed out as a hypothesis, that to promote a solid formation of teachers is a prerequisite for facing the challenges of teaching practice. Practice that shown for the present discussion, as the link between the health of teachers and students. Moving in the direction of taking as objectives of this study provide theoretical support for health promotion within school education, taking as reference the process of teacher training; and demonstrate, from the theoretical framework of cultural historical psychology and pedagogy historical-critical, the relationship of conditionality between the solid quality of teacher education and health promotion of teachers and students. To this end, we resort to theoretical research, which works by contributing of the analysis socio-political of education. This texts contribute to the understanding the relationships between education and psychological development of individuals as well as propositions about the nature of education school teaching and the pressing need for restructuring the school as objective to optimize the development humanization condition of the people. The selection of works guide this research thru the historical and dialectical materialism, because the thought of Marx endeavored to scientifically understand the laws of the humanization process. Thus shows the path of the historic cultural psychology, when trying to explain the development of the human psyche as a convergence of multiple factors (biological and social) that relate to a dynamic process of constant transformation ...

Esse trabalho tem como objeto o papel do ensino na promoção de saúde, sendo que para isso não podemos prescindir da análise do binômio saúde/adoecimento de professores e alunos. Parte-se da hipótese de que a criação das condições para a formação e o autodomínio dos processos funcionais psíquicos superiores no âmbito da educação escolar impõe-se como uma das condições que corroboram a promoção da saúde. Isto é, aponta-se como hipótese que a implantação de um projeto pedagógico que possibilite e valorize uma sólida formação tanto de professores quanto de alunos é uma das condições para o enfrentamento dos desafios impostos pela prática pedagógica. Prática essa que se mostra para a presente discussão, como o elo entre a saúde de professores e alunos. Como objetivos desse estudo, busca-se fornecer subsídios teóricos para a promoção de saúde no âmbito da educação escolar, tomando-se como referência para tanto o processo de formação de professores; bem como demonstrar, a partir do aporte teórico da psicologia histórico cultural e da pedagogia histórico-crítica, a relação de condicionalidade recíproca entre a sólida qualidade da formação de professores e a promoção da saúde de professores e alunos. Para tanto, recorre-se à pesquisa teórica, pela qual serão enfocadas obras que contribuem para a análise sócio-política da educação escolar, para a compreensão das relações entre a educação escolar e o desenvolvimento psíquico dos indivíduos, assim como proposições acerca da natureza da educação escolar e a premente necessidade de reestruturação pedagógica da escola como condição objetiva para otimizar o desenvolvimento, a humanização das pessoas. A seleção das obras que orientam essa pesquisa assenta-se no materialismo histórico-dialético, pois o pensamento de Marx empenhou-se em compreender cientificamente as leis de transformação e desenvolvimento do processo ...
Keywords: Educação; Educação - Estudo e ensino; Psicologia escolar; Education